2019
DOI: 10.3390/molecules24234379
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Norsesquiterpenoids and Triterpenoids from Populus euphratica Resins

Abstract: Two new octanorlanostane-type triterpenes, euphraticanoids A and B (1 and 2), two new trinorsesquiterpenoids, euphraticanoids C and D (3 and 4), and eight known triterpenoids (5, 6, 8–13) along with one steroid (7) were isolated from Populus euphratica resins. The structures of these new compounds, including their absolute configurations, were characterized by spectrocsopic, chemical, and computational methods. Biological evaluation revealed that compounds 4, 7–9, 12, and 13 display neuroprotective activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The results of this last work indicated that these triterpenoids have strong neuroprotective effects via antioxidant response element gene activation and decreased the level of glutamate uptake. Other norsesquiterpenoids and triterpenoids isolated from Populus euphratica resins have also demonstrated neuroprotective activities in H 2 O 2 -induced HT-22 cells, and in glutamate-induced SH-SY5Y cells ( 47 ). However, the effect of triterpenes in the lipid alteration related to AD has never been studied.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this last work indicated that these triterpenoids have strong neuroprotective effects via antioxidant response element gene activation and decreased the level of glutamate uptake. Other norsesquiterpenoids and triterpenoids isolated from Populus euphratica resins have also demonstrated neuroprotective activities in H 2 O 2 -induced HT-22 cells, and in glutamate-induced SH-SY5Y cells ( 47 ). However, the effect of triterpenes in the lipid alteration related to AD has never been studied.…”
Section: Discussionmentioning
confidence: 99%
“…It is responsible for the characteristic odour of freshly turned earth and is associated with unpleasant off-flavors in water [154][155][156][157], wine and fish [158]. Euphraticanoid D (27) (Figure 4) was isolated from Populus euphratica resins [152]. The structure of this new compound, including its absolute configuration, was characterized by spectroscopic, chemical and computational methods.…”
Section: Geosmin Derivativesmentioning
confidence: 99%
“…In that work, a new tri-nor-guaiane, euphraticanoid C (82), was isolated and characterized by spectroscopic, chemical, and computational methods. The neuroprotective properties of this compound were observed in glutamate-induced SH-SY5Y cells and proved that euphraticanoid C (82) could dose-dependently protect neural cell injury[152].Trinoranastreptene(83), which was first isolated from the cultured cells of the liverwort Calypogeia granulata Inoue (Figure8)[239], is a tricyclic tri-nor-sesquiterpene that has an unprecedented tricyclo[5.3.01,6 .0]decane ring system. Its structure was determined by detailed NMR analysis, and it turned out to be identical or antipodal to the clavukerin B from Okinawan soft coral (stolonifer) Clavularia koellikeri[240,241] and inflatene from the stoloniferan coral Clavularia inflata var.…”
mentioning
confidence: 98%
“…It can be expected that the treatment of neurodegenerative diseases, because of their complexity, require multi-target drugs [ 5 ]. Neuroprotection strategy is well-established and has been described for a number of small molecules with different molecular mechanisms: tacrine and its congeners [ 6 ], anxiolytic compound afobazol [ 7 ], and many natural compounds [ 8 ]. Interestingly, neuroprotective activity has been also reported for antipsychotic haloperidol, multifunctional D 2 -like dopamine, and sigma receptor subtype antagonist [ 9 ].…”
Section: Introductionmentioning
confidence: 99%